An Analysis of Road Traffic Accidents in Rajbiraj Municipality, Nepal: Pre versus Post-Covid Comparison - Telee, Lal Babu Sah; Yadav, Umesh Kumar (Rupantaran: A Multidisciplinary Journal, 2026)
Road traffic accidents is an important public safety concern in Nepal. This study reveals a descriptive and exploratory analysis of officially reported annual road traffic accident data. The data is from Rajbiraj Municipality for the period 2019–2024 which include pre and post covid period. The dataset consists of counts of vehicle accidents, human deaths, injuries, and animal casualties. Study focuses on descriptive statistics, rate calculations, correlation study, and an exploratory Poisson regression model. Results of the study demonstrate a substantial increase in reported accidents after 2020, from mean annual accidents 359.5 in 2019–2020 to 1,794.0 in 2021–2024. During the same time, fatalities per 1,000 accidents decreased markedly over the study period. Results of Poisson regression revels that variation in accident counts alone does not adequately explain year-to-year changes in fatalities. Overall, the study concludes that while road traffic accidents increased substantially during the post-COVID period, fatality rates per 1,000 accidents declined indicating changes in accident severity or emergency response effectiveness. This finding focuses the necessity of strengthened municipal road safety strategies and systematic data collection for evidence- based interventions.